Web‐based collaborative care intervention to manage cancer‐related symptoms in the palliative care setting. Issue 8 (11th March 2016) - Steel, Jennifer L.; Geller, David A.; Kim, Kevin H.; Butterfield, Lisa H.; Spring, Michael; Grady, Jonathan; Sun, Weiing; Marsh, Wallis; Antoni, Michael; Dew, Mary Amanda; Helgeson, Vicki; Schulz, Richard; et al.
Abstract : BACKGROUND: The aim of this study was to examine the efficacy of a collaborative care intervention in reducing depression, pain, and fatigue and improve quality of life. METHODS: A total of 261 patients with advanced cancer and 179 family caregivers were randomized to a web‐based collaborative care intervention or enhanced usual care. The intervention included the following: 1) a web site with written and audiovisual self‐management strategies, a bulletin board, and other resources; 2) visits with a care coordinator during a physician's appointment every 2 months; and 3) telephone follow‐up every 2 weeks. Primary patient outcomes included measures of depression, pain, fatigue, and health‐related quality of life. Secondary outcomes included Interleukin (IL)‐1α, IL‐1β, IL‐6, and IL‐8 levels, Natural Killer (NK) cell numbers, and caregiver stress and depression. RESULTS: At the baseline, 51% of the patients reported 1 or more symptoms in the clinical range. For patients who presented with clinical levels of symptoms and were randomized to the intervention, reductions in depression (Cohen's d = 0.71), pain (Cohen's d = 0.62), and fatigue (Cohen's d = 0.26) and improvements in quality of life (Cohen's d = 0.99) were observed when compared to those in the enhanced usual car arm at 6 months. Reductions in IL‐6 (φ = 0.18), IL‐1β (φ = 0.35), IL‐1α (φ = 0.19), and IL‐8 (φ = 0.15) and increases in NK cell numbers (φ = 0.23) were observed in comparison with enhanced usual care arm at 6 months. Reductions in caregiver stress (Cohen's d = 0.75) and depression (Cohen's d = 0.37) were observed at 6 months for caregivers whose loved ones were randomized to the intervention arm. CONCLUSIONS: The integration of screening and symptom management into cancer care is recommended. Cancer 2016;122:1270–82 . © 2016 American Cancer Society . Abstract : A stepped web‐based collaborative care intervention reduces symptoms, improves quality of life, and decreases inflammation for patients receiving palliative care for cancer. Furthermore, the intervention reduces caregiver stress and depression.